2021
DOI: 10.1021/acssynbio.1c00357
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Single Pan-Specific Ubiquibodies for Targeted Degradation of All Forms of Endogenous ERK Protein Kinase

Abstract: Ubiquibodies (uAbs) are a customizable proteome editing technology that utilizes E3 ubiquitin ligases genetically fused to synthetic binding proteins to steer otherwise stable proteins of interest (POIs) to the 26S proteasome for degradation. The ability of engineered uAbs to accelerate the turnover of exogenous or endogenous POIs in a post-translational manner offers a simple yet robust tool for dissecting diverse functional properties of cellular proteins as well as for expanding the druggable proteome to in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…While protein stability varies, proteins are generally more stable than mRNA, both in storage and in biological media [ 41 ]. Finally, it has been reported that some therapeutically interesting proteins are poorly expressed as transgenes despite facile purification from E. coli cultures [ 42 ]. Thus, for some applications, nucleic acids may be precluded entirely as a treatment modality, and direct protein delivery could be the only method for introducing potent therapeutics into the cytoplasm.…”
Section: Comparison Of Protein Delivery To Conventional Drug Modalitiesmentioning
confidence: 99%
“…While protein stability varies, proteins are generally more stable than mRNA, both in storage and in biological media [ 41 ]. Finally, it has been reported that some therapeutically interesting proteins are poorly expressed as transgenes despite facile purification from E. coli cultures [ 42 ]. Thus, for some applications, nucleic acids may be precluded entirely as a treatment modality, and direct protein delivery could be the only method for introducing potent therapeutics into the cytoplasm.…”
Section: Comparison Of Protein Delivery To Conventional Drug Modalitiesmentioning
confidence: 99%
“…All purified uAb constructs, and unfused CHIPΔTPR were obtained from cultures of E. coli BL21(DE3) cells carrying pET28a-based plasmids encoding the SnP_7 the SnP_8 uAbs or CHIPΔTPR. 26 Cells were grown in Luria-Bertani (LB) medium according to protocols described previously. 26 Briefly, protein expression was induced with 1M isopropyl β-D-1-thiogalactopyranoside (IPTG) when the culture density, determined by optical density at 600 nm (OD 600 ), reached 0.5-0.7 and proceeded for 12-16 h at 37°C.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…26 Cells were grown in Luria-Bertani (LB) medium according to protocols described previously. 26 Briefly, protein expression was induced with 1M isopropyl β-D-1-thiogalactopyranoside (IPTG) when the culture density, determined by optical density at 600 nm (OD 600 ), reached 0.5-0.7 and proceeded for 12-16 h at 37°C. Following expression, cells were harvested by centrifugation at 10,000 x g for 10 min at 4 °C.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that the E40 DARPin binds to unphosphorylated ERK 43,44 and prevents phosphorylation and activation by MEK 43 . However, as E40 had previously been shown only to prevent phosphorylation of chimeric exogenous ERK 43 , we first established that E40 can inhibit endogenous ERK activity in a live-cell assay.…”
Section: Regulating Endogenous Kinase Activitymentioning
confidence: 99%